Do women want disclosure of fetal gender during prenatal ultrasound scan?. (2010)
Background/Objectives: It is possible that not all women would want the disclosure of fetal gender by the sinologist during a prenatal scan. The objectives of this study were to determine the proportion of women who do not want fetal gender disclosure at the time of prenatal ultrasonography and document their reasons. Method: A cross-sectional survey of women that were 20 weeks or more pregnant that had prenatal ultrasound at a private health facility in January 2006. The sonologist asked each of the women during the procedure whether they wanted to know fetal sex or not. Those that consented had disclosure of fetal sex while those that declined gave their reasons, which were documented. Results: Two hundred and one (201) women were studied within the study period. Most of the women (82%) were of the Hausa/Fulani ethnic group and were predominantly of the Islamic faith (90%). One hundred and ninety women (94.5%) consented to disclosure of fetal gender, while eleven (5.5%) declined. The main reason for not wanting to know fetal sex was: ‘Satisfied with any one that comes’. Conclusion: Most of the pregnant women (94%) would want disclosure of fetal gender at prenatal ultrasound scan. Only 5.5% of the women would not want fetal sex disclosure because they were satisfied with whichever that was there. It is advisable for the sonologist to be discrete on what to say during the procedure especially as it relates to fetal sex so as not to hurt those that do not want disclosure